2022
DOI: 10.21608/asnj.2022.127397.1343
|View full text |Cite
|
Sign up to set email alerts
|

Health Belief Model-based educational program about cervical cancer prevention on women knowledge and beliefs

Abstract: Background: Cervical cancer affects around half a million women each year, and the illness claims the lives of nearly 300,000 people globally. The illness is largely avoidable. Cervical cancer is the second most frequent cancer in women worldwide, and it is a major public health issue in poor nations. Aim of the study: This study aimed to evaluate the effect of health Belief Model-based educational program about cervical cancer prevention on women knowledge and beliefs. Subjects and Method: This study used a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 4 publications
(4 reference statements)
2
10
0
Order By: Relevance
“…In addition, the intervention led to a significant increase in perceived benefits and a significant decrease in perceived barriers in the intervention group. Also, a similar study based on the Health Belief Model conducted through Telegram 27 and the other previous studies confirm the current findings 10,11,13,26 . In fact, the present study demonstrated the importance and benefits of Pap smear testing and removed mental barriers by employing a midwife and utilizing her lecture and teachings.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In addition, the intervention led to a significant increase in perceived benefits and a significant decrease in perceived barriers in the intervention group. Also, a similar study based on the Health Belief Model conducted through Telegram 27 and the other previous studies confirm the current findings 10,11,13,26 . In fact, the present study demonstrated the importance and benefits of Pap smear testing and removed mental barriers by employing a midwife and utilizing her lecture and teachings.…”
Section: Discussionsupporting
confidence: 90%
“…In another study, which was conducted in Iran, three face‐to‐face training sessions based on the constructs of the Health Belief Model were implemented for 80 rural women, and similar results were reported 11 . Also, the results of other previous studies are consistent with these results 10,26,27 . The current educational intervention using techniques such as lectures and question and answer led to an increase in individuals' perception of the risk of disease.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…[ 5 ] Thus, to increase cervical cancer screening uptake among women, it is necessary that their perception of threat regarding cervical cancer be enhanced. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%